2020
DOI: 10.1016/j.canlet.2020.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin acts as a molecular switch to determine SPARC function in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest of all solid tumours and more effective therapy is urgently needed. The stroma is thought to play a critical role in tumour development and metastasis, and high stromal expression of the matricellular protein SPARC has been robustly associated with poor patient prognosis. However, the precise role of SPARC has been highly controversial, with multiple studies demonstrating tumour-suppressor properties of this protein in vitro. This conflicting data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…SPARC, which is also called osteonectin, is a component of the bone matrix that modulates cellular interactions with the extracellular matrix, exerting an adhesive, promigratory effect on cells. [72][73][74] Studies confirmed that high expression of SPARC in most of the tumors with a tendency for bone metastasis. 75,76 In PCa, Sarmishtha De et al treated tumor cells with different antagonists and conclude that tumor cells on the bone surface linked with SPARC exhibit αvβ3 expression.…”
Section: Vegf Promotes Pca Bone Metastasis By Controlling αVβ3 and Spmentioning
confidence: 72%
“…SPARC, which is also called osteonectin, is a component of the bone matrix that modulates cellular interactions with the extracellular matrix, exerting an adhesive, promigratory effect on cells. [72][73][74] Studies confirmed that high expression of SPARC in most of the tumors with a tendency for bone metastasis. 75,76 In PCa, Sarmishtha De et al treated tumor cells with different antagonists and conclude that tumor cells on the bone surface linked with SPARC exhibit αvβ3 expression.…”
Section: Vegf Promotes Pca Bone Metastasis By Controlling αVβ3 and Spmentioning
confidence: 72%
“…switched the function of SPARC from promoting cancer cell proliferation to growth inhibition and induction of apoptosis (Munasinghe et al, 2020). Although BGLAP was known crucial during bone remodeling, the function remained largely unknown and it arose great interest recently as a bone-derived hormone in regulation of energy metabolism (Li et al, 2016;Zoch et al, 2016;Mera et al, 2018;Moser and van der Eerden, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It’s worth noting that the influence of SPARC on tumor progression depended on the initiating cell type, tumor stage and context of the microenvironment ( Tai and Tang, 2008 ; Arnold and Brekken, 2009 ; Rossi et al, 2016 ). Notably, Munasinghe et al reported that depletion of fibronectin switched the function of SPARC from promoting cancer cell proliferation to growth inhibition and induction of apoptosis ( Munasinghe et al, 2020 ). Although BGLAP was known crucial during bone remodeling, the function remained largely unknown and it arose great interest recently as a bone-derived hormone in regulation of energy metabolism ( Li et al, 2016 ; Zoch et al, 2016 ; Mera et al, 2018 ; Moser and van der Eerden, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor activity of EMAP II is mediated through targeted interference with stroma fibronectin-integrin dependent pancreatic cancer cell proliferation [96]. New findings indicate that the depletion of fibronectin switches the activity of secreted protein acidic cysteine-rich (SPARC) from promoting cancer cell proliferation to growth inhibition and induction of apoptosis [97].…”
Section: Modulation Of Cafs To Treat Pancreatic Cancermentioning
confidence: 99%